Pengaruh Disiplin Kerja Terhadap Prestasi Kerja Karyawan Pada PT Bank Sulselbar Cabang Pembantu Kahu - Andi Tri Rezeki Aulia; Anwar Ramli; M. Ikhwan Maulana Haeruddin; Uhud Darmawan Natsir; Muh. Ichwan Musa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This research aims to determine whether there is an influence of work discipline on increasing employee work performance. The type of research used is Quantitative Descriptive. The data processed is the result of distributing questionnaires to employees of PT Bank Sulselbar Branch Pembantu Kahu. Using a population of 30 people and a sample of 30. The data analysis technique used is simple linear regression. Based on the research results, work discipline has a positive and significant effect on employee work performance at PT Bank Sulselbar Branch Pembantu Kahu.